High School Physics Assessments in Bontang City: Fostering Higher-Order Thinking - Wati, Asma; Qadar, Riskan; Sulaeman, Nurul Fitriyah (FKIP ULM, 2024)
This research aims to determine the percentage of HOTS-level physics questions and the cognitive level and dimensions of knowledge of HOTS-level physics questions on the class X SMAN/MAN summative exam in Bontang. These questions were analysed based on Bloom's revised taxonomy: cognitive level and knowledge dimensions. The type of research used in this research is descriptive research with a quantitative approach. The subject of this research was four schools in Bontang city, including high schools A, B, C, and D. Data collection techniques use documentation techniques. The results of the research show that the percentage of HOTS-level physics questions is 12.2%, with the percentage of each question code being 5% for question code A, 15% for question code B, 20% for question code C, and 16% for question code D for cognitive level C4.In contrast, cognitive levels C5 and C6 are not found in the summative exam question document. The cognitive level in the summative exam questions includes C1 to C4 and factual, conceptual and procedural knowledge dimensions. The knowledge dimension in the HOTS level question is dominated by the procedural knowledge dimension, while there is only one question in the conceptual knowledge dimension. Future physics should consider the balance of cognitive level and dimension in school assessment.